PROBLEMS AND SOLUTIONS OF ENVIRONMENTAL STABILITY OF CENTRAL ASIA - Atajanova Muyassar Atajanovna (Journal of new century innovations, 2023)
Abstract: Ecology (ancient Greek: oīkos - "house", "dwelling place") - systems that are higher than the organism at different levels; a set of biological sciences that study the structure of populations, biocenoses, biogeocenoses (ecosystems) and the biosphere, and the processes taking place in them. Ecology is also interpreted as a science that studies the interaction between organisms and their environment. This article explains about the ecological situation in Central Asia.